Grazing Changed Plant Community Composition and Reduced Stochasticity of Soil Microbial Community Assembly of Alpine Grasslands on the Qinghai-Tibetan Plateau - Li, Yu; Dong, Shikui; Gao, Qingzhu; Fan, Chun; Fayiah, Moses; Ganjurjav, Hasbagan; Hu, Guozheng; Wang, Xuexia; Yan, Yulong; Gao, Xiaoxia; Li, Shuai (Frontiers in Plant Science, 2022)
Grazing is a substantial threat to the sustainability of grassland ecosystems, and uncertainty about the variation of plant and soil microbial community and the linkages between them limits the comprehensive understanding of grazing ecology. We conducted an experiment on the effects of the grazing regimes rotational grazing (RG), continuous grazing (CG), and grazing exclusion (GE) on an alpine meadow on the Qinghai-Tibetan Plateau, explored the plant community composition, soil microbial community assembly mechanism, taxonomically and functionally composition among grazing regimes, then assessed the relationship between plant species and the soil microbes by constructing a co-occurrence network. The results showed that the plant community composition was different among the grazing regimes, while the soil microbial community composition did not show any difference. RG and CG had similar soil bacterial functional composition, while GE and RG had similar soil fungal functional composition. The soil microbial community in all grazing regimes assembled mainly according to stochastic rather than deterministic mechanisms, and RG and CG reduced the relative importance of stochastic ratio. At the microbial phylum level, in comparison to GE, CG increased Acidobacteria and Armatimonadetes, and RG increased Elusimicrobia. In the network of plant species and soil microbial classes, internal members of plants, bacteria, fungi and archaea were mainly positively linked (symbiosis and promotion), while plants and soil microbes were mainly negatively linked (competition). There were 5 microbial generalists in the network, which connected with many microbes, and four showed no difference in their abundance among the grazing regimes. Overall, the stable key microbes in the network and the fact that most of the plants were not connected with microbes weakened the impact of grazing-induced changes in the plant community on soil microbes, probably resulting in the stable soil microbial community composition. Moreover, there was still a dominant and tolerant species, Kobresia pygmaea, that connected the plant and microbial communities, implying that the dominant plant species not only played a crucial role in the plant community but also acted as a bridge between the plants and soil microbes; thus, its tolerance and dominance might also have stabilized the soil microbial community.